Vegetated landscape coherence and complexity shape psychophysiological stress recovery in campus courtyards - Yaling Gao; Qunyue Liu; Wenxin Yang; Lingfang Lin; He Huang (PLoS ONE, 2026)
University students across urban campuses face sustained stress loads, making everyday restorative opportunities paramount. We ran a randomized virtual-reality experiment (N = 282) crossing landscape coherence (low, moderate, high) and complexity (low, moderate, high) in teaching-building courtyards, plus a non-vegetated control, to interrogate how designable visual attributes govern recovery. Complexity was parameterized with Shannon entropy while coherence reflected planting order. Heart rate, RMSSD, skin conductance level (SCL), and the Perceived Restorativeness Scale (PRS) were collected across baseline, stress, and recovery phases. Vegetated scenes improved SCL and PRS relative to the control. PRS rose monotonically with complexity and peaked at moderate-to-high coherence. Crucially, coherence moderated SCL responses: biodiversity-rich scenes only delivered autonomic settling when ordered, revealing a conditional mechanism that ties information-processing theory to stress-reduction pathways. The entropy-guided framework therefore refines prevailing restorative theories and yields a portable VR protocol that international teams can adapt with local species palettes. The findings translate into globally relevant guidance for campus and urban designers seeking micro-restorative infrastructure in dense settings.